Profile shape variation and sexual dimorphism amongst middle-aged Northern Europeans. (2nd April 2021) - Kanavakis, Georgios; Silvola, Anna-Sofia; Halazonetis, Demetrios; Lähdesmäki, Raija; Pirttiniemi, Pertti
Summary: Aim: To explore profile shape variation in a large population of middle-aged individuals and investigate features of sexual dimorphism. Materials and methods: Facial profile photographs of 1776 individuals (964 females and 812 males; 46 years old), members of the Northern Finland Birth Cohort 1966 (NFBC1966), were uploaded and digitized with Viewbox software. Profile shape was defined with 47 landmarks (4 fixed and 43 sliding semi-landmarks). Digitized images were reoriented and scaled with Procrustes Superimposition, and shape variation was determined with a Principal Component Analysis. Results: More than 90 per cent of profile shape variation was explained by Principal Components (PC) 1–9. PC1, explaining the largest amount of variation (33.1 per cent) described changes in facial convexity, slope of the forehead, lip, and chin protuberance. PC2 (23.1 per cent variation) was more related to vertical changes of the lower facial third and PC3 (11 per cent variation) primarily described changes in lip protrusion and nasal projection. Shape analysis showed a significant difference between the average female and the average male profile shape ( P < 0.001); however, this was not evident upon visual observation. The shape variable most associated with sex was PC3 (η 2 = 0.245; P < 0.001), which described changes in lip prominence and in projection of the dorsal nasal surface. An additional discriminant analysis showed that profile shape predicted sex in 76 per cent of males and 79.6 per cent of females. Conclusions: There is significant sexual dimorphism in facial profile among middle-aged adults. Profile shape variation was associated to changes in lip protrusion, nasal protuberance, and chin projection.